2017
DOI: 10.1038/npp.2017.73
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length in Newborns is Related to Maternal Stress During Pregnancy

Abstract: Telomere length (TL) is a marker of biological aging, and numerous studies have shown associations between TL and somatic or psychiatric disorders. Research also indicates an association between maternal stress during pregnancy and TL in the offspring. The present study investigated possible associations between TL and: (1) maternal perceived stress during pregnancy; (2) a maternal lifetime history of psychiatric disorder (lifetime PD); and (3) paternal age. TL was analyzed in 319 newborns and 318 mothers from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 43 publications
(45 reference statements)
6
64
2
2
Order By: Relevance
“…Additionally, a correlation between the effects of prenatal exposures and maternal conditions such as obstetric complications, BMI, state of nutrition, stress and sociologic status during pregnancy, and disadvantageous birth outcomes of offspring in telomere length manner was shown [49][50][51]. For example, the association between maternal stress during pregnancy and shorter offspring telomere length was confirmed by many authors [52][53][54]. Other authors revealed an association between low birth weight and shorter telomere length in peripheral blood mononuclear cells in preschool aged children [55].…”
Section: Telomere Assessment and Clinical Outcomehigh Hopesmentioning
confidence: 82%
“…Additionally, a correlation between the effects of prenatal exposures and maternal conditions such as obstetric complications, BMI, state of nutrition, stress and sociologic status during pregnancy, and disadvantageous birth outcomes of offspring in telomere length manner was shown [49][50][51]. For example, the association between maternal stress during pregnancy and shorter offspring telomere length was confirmed by many authors [52][53][54]. Other authors revealed an association between low birth weight and shorter telomere length in peripheral blood mononuclear cells in preschool aged children [55].…”
Section: Telomere Assessment and Clinical Outcomehigh Hopesmentioning
confidence: 82%
“…Maternal stress during pregnancy, but not her lifestyle, also lead to the shortening of the telomere length in newborns. The fact that the relationship between maternal prenatal stress and the telomere length was observed in offspring but not in mothers can be explained by high vulnerability to stress of a maturing organism during foetal development (Send et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Finally, it was demonstrated that maternal lifetime history of a psychiatric disorder causes shortening of maternal TL but does not affect newborn TL. Acute stress during pregnancy, on the other hand, is related to shorter TL of a newborn but does not affect the mother's TL [95].…”
Section: Maternal Stressmentioning
confidence: 94%
“…TL in children can be affected by oxidative, immune, endocrine and metabolic pathways in a way that accelerates cellular dysfunction over the lifespan [11,92], thus reflecting the effect of specific conditions on the later susceptibility to a disease. Maternal stress [93][94][95], hormones [96], smoking [97], race [98], vitamin concentrations [99,100], pre-pregnancy body mass index (BMI) [101] and other factors showed correlation with TL and pointed out the importance of in utero exposures in the regulation of newborn TL. In this section we will focus on some of the most pertinent antenatal determinants.…”
Section: Determinants Of Newborn Tlmentioning
confidence: 99%